Effect‐directed identification of endocrine disruptors in plastic baby teethers. Issue 11 (18th May 2015) - Berger, Elisabeth; Potouridis, Theodoros; Haeger, Astrid; Püttmann, Wilhelm; Wagner, Martin
Abstract Concerns have been raised regarding the human health effects of endocrine disrupting chemicals (EDCs), many of which are associated with and leaching from plastics. As infants are particularly vulnerable to EDCs, we have investigated whether plastic teethers for babies represent a relevant source of exposure. Applying effect‐directed analysis, we use bioassays to screen teethers, toys used to soothe a baby's teething ache, for endocrine activity and chemical analysis to identify the causative compounds. We detected significant endocrine activity in two of 10 plastic teethers. Those samples leached estrogenic and/or antiandrogenic activity as detected in the Yeast Estrogen Screen and Yeast Antiandrogen Screen. After sample fractionation, gas chromatography–mass spectrometry non‐target screening revealed that methyl‐, ethyl‐ and propylparaben were responsible for the observed estrogenic and antiandrogenic activity in one product. The second product is likely to contain at least six different antiandrogenic compounds that remain so far unidentified. This study demonstrates that plastic teethers can be a source of infant exposure to well‐established and unknown EDCs. Because of their limited value to the product, but potential toxicity, manufacturers should critically revisit the use of parabens in plastic teethers and further toys. Moreover, plastic teethers might leach EDCs that escape routine analysis and, thus, toxicological evaluation. The resulting uncertainty in product safety poses a problem to consumers, producers and regulators that remain to be resolved. Copyright © 2015 John Wiley & Sons, Ltd.